Measurements of single-phase and two-phase flows in a vertical pipe using ultrasonic pulse Doppler method and ultrasonic time-domain cross-correlation method - Nguyen, Tat Thang; Kikura, Hiroshige; Duong, Ngoc Hai; Murakawa, Hideki; Tsuzuki, Nobuyoshi (Vietnam Journal of Mechanics, 2013)
Ultrasonic Velocity Profile (UVP) method for measurement of single-phase and two-phase flow in a vertical pipe has recently been developed in the Laboratory for industrial and Environmental Fluid Dynamics, Institute of Mechanics, VAST. The signal processings of the UVP method include the ultrasonic pulse Doppler method (UDM)and the ultrasonic time-domain cross-correlation (UTDC) method. For two-phase flow, simultaneous measurements of both liquid and gas are enabled by using a multi-wave ultrasonic transducer (multi-wave TDX). The multi-wave TDX is able to emit and receive ultrasound of two different center frequencies of 2 MHz and 8 MHz at the same time and position. 2 MHz frequency with beam diameter 10 mm is exploited for measurement of gas. 8 MHz one with beam diameter 3 mm is used for liquid. Measurements have been carried out for laminar and turbulent single-phase flows and bubbly counter-current two-phase flows in two flow loops using two vertical pipes of 26 mm inner diameter (I.D.) and 50 mm I.D. respectively. Based on the measured results, assessment of each method is clarified. Applicability of each method for different conditions of pipe flow has been tested. Suggestions for application of the two methods have been recommended.